Contemporary Theological Issues - Nur Azizah, Liza; Fahmi, Muhammad Imran; Atiah, Umi; Putra, Deko Rio (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Contemporary issues faced by Muslims are closely linked to global political dynamics and rapid technological developments. Foreign policies of several Western countries are often perceived as interventions in the Muslim world, triggering resistance and conflict that influence Islamic thought and give rise to various theological responses. At the same time, technological advancement accelerates the penetration of global culture, bringing values such as secularism, pluralism, consumerism, and individualism. Objective: This study aims to understand emerging contemporary issues and to analyze how Islamic theology (kalam) responds to secularism, pluralism, radicalism, and technological modernity. It also seeks to reaffirm the true teachings of Islam in accordance with Islamic law through a contextual and critical approach. Method: The research employs a qualitative method using a library study approach. It analyzes the concept of aqidah and rational arguments in the science of kalam, while tracing its development from classical to contemporary periods in responding to modern challenges. Findings and Implications: The study finds that kalam provides a normative and rational foundation to address modern beliefs and global issues. Inspired by Muhammad Iqbal’s emphasis on ijtihad, theology must encourage independent reasoning as a dynamic principle within Islam. This approach enables Muslims to critically engage with technological and global transformations. Conclusion: Kalam remains relevant in confronting contemporary technological and ideological challenges. Through critical ijtihad and contextual understanding, Islamic theology offers guidance to navigate modernity while preserving authentic Islamic principles.